Effects of salinity on growth, competitive interaction and total nitrogen content of two estuarine macrophyte species cultivated on artificial substrate - Nunes, Laís Samira Correia [UNESP]; Camargo, Antonio Fernando Monteiro [UNESP] (Springer Nature, 2020)
Salinity can compromise the growth of aquatic macrophytes, influencing their nutrient content and interspecific interactions. In estuaries, the sediment characteristics vary in salinity as well as nutrient availability, granulometry and microbiota. The use of artificial substrates in manipulative experiments allows the evaluation of the isolated effect of salinity on plants. We evaluated the effects of salinity on growth, interspecific interaction and total nitrogen (TN) content of the estuarine macrophytes Spartina alterniflora and Crinum americanum cultivated on expanded vermiculite. We conducted a two-factor experiment (3 cultures × 3 salinities × 5 replicates = 45 experimental units) lasting 185 days in a greenhouse. We cultivated monocultures (8:0 and 0:8) and mixed cultures (4:4) at 0, 20 and 30 ppt salinity levels with the same concentration of nutrient solution. We found that salinity did not influence the growth of S. alterniflora and C. americanum in monoculture. In mixed culture, there was an asymmetric competition, as S. alterniflora limited the growth of the aboveground fraction of C. americanum at higher salinity; however, C. americanum did not limit the growth of S. alterniflora at any treatment. Salinity did not influence the TN content in S. alterniflora. However, C. americanum had greater TN content in the aboveground fraction at higher salinity, possibly as a strategy of salt tolerance. The TN content in the aboveground fraction of C. americanum was lower in the mixed cultures than in the monocultures, indicating an effect of the interspecific interaction.
Keywords: Crinum americanum; Expanded vermiculite; Interspecific competition; Nitrogenous compounds; Salt stress; Spartina alterniflora